2020
DOI: 10.1289/ehp4178
|View full text |Cite
|
Sign up to set email alerts
|

Airway Hyperresponsiveness, Inflammation, and Pulmonary Emphysema in Rodent Models Designed to Mimic Exposure to Fuel Oil–Derived Volatile Organic Compounds Encountered during an Experimental Oil Spill

Abstract: BACKGROUND: Fuel oil-derived volatile organic compounds (VOCs) inhalation is associated with accidental marine spills. After the Prestige petroleum tanker sank off northern Spain in 2002 and the Deepwater Horizon oil rig catastrophe in 2009, subjects involved in environmental decontamination showed signs of ongoing or residual lung disease up to 5 y after the exposure. OBJECTIVES: We aimed at investigating mechanisms driving persistent respiratory disease by developing an animal model of inhalational exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Moreover, the present study dealt with leaded gasoline, where lead was reported to affect the immune response either in humans 11 or animals 9 . Amor-Carro et al 15 explained that lead exposure could stimulate cascade events, including oxidative stress and inflammation, accompanied by reduced immune status. Moreover, the current study exhibited a significant increase in Bax expression and a decrease in Bcl2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the present study dealt with leaded gasoline, where lead was reported to affect the immune response either in humans 11 or animals 9 . Amor-Carro et al 15 explained that lead exposure could stimulate cascade events, including oxidative stress and inflammation, accompanied by reduced immune status. Moreover, the current study exhibited a significant increase in Bax expression and a decrease in Bcl2.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Amor-Carro et al 15 attributed cell death to the increased formation of ROS, which leads to oxidative damage of mitochondrial DNA. Su et al 40 recommended that lipid peroxidation may serve as a common mediator of apoptosis in response to toxicants and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, investigations [ 92 , 111 118 ] were conducted to evaluate the toxicity of inhaled COV generated from Deep Water Horizon (DWH) surrogate crude oil in a rat model to gain a greater understanding of the adverse health effects of COV inhalation in upstream petroleum workers [ 49 , 74 , 119 ]. The DWH surrogate crude oil provided by British Petroleum (BP) Exploration and Production, Inc., similar to the oil associated with the 2010 Deepwater Horizon spill from the Macondo Well in Mississippi Canyon Block 252, was characterized in McKinney et al [ 95 ].…”
Section: Pathophysiological Effects Of Cov Exposure In Animal Modelsmentioning
confidence: 99%